Ferramenta para promover a economia circular em propriedades rurais - Barros, Murillo Vetroni (2019)
Unlike the linear model "take-make-use-dispose", the circular model "grow-make-userestore" intends to potentiate material and energy flows within the system with the premise of increasing environmental gains. Circular economy practices can be alternatives when used in the agricultural sector, with closed-loop material and energy initiatives and promoting greater internal value adding. The circular performance in the agro sector can be considered a problem in face of the lack of consistent tools and methods for its measurement. In order to generate more internal value and competitive advantage in agribusiness, this research presents as general objective to identify potential opportunities for value adding from external flows to support the circular economy in rural properties. It was observed through a systematic literature review that there are no similar tools in the literature to measure the circularity of organizations in terms of material and energy flows, to promote circular economy and to allow greater internal value adding in rural properties. The tool is based on a set of graphical representations and quantitative indicators. For the graphical visualization, the software R (and the Circlize package) was used. The quantitative indicators show a circularity index ranging from 0% to 100%, which can be assessed on different levels. For the results, the tool was applied in a rural property, however the tool can be used in different organizations and processes. The necessary information in terms of material and energy flows was obtained by applying a questionnaire to the rural property`s owner. In the study carried out, 11 processes in the rural property, and 4 generic processes, were added, which have material exchanges with the rural property. The rural property presents more than 40 material and energy flows showing internal exchanges, with neighbors and with the cooperative. The circular graph was presented containing 15 processes (for material) and nine processes (for energy) with flows of inputs, outputs and their quantities. Circularity indicators showed that the rural property has 65% of circularity (for material) and 25% of circularity (for energy). Adding the neighboring properties in the circular analysis, the indicator rises to 73% in terms of material. Applying the indicator at the cooperative level, the circularity rises to 75% in terms of material. In this sense, approximately ¾ of the material flows of the rural property circulate within the cooperative activities. This shows a high involvement of the rural property with the cooperative, which generates greater internal value, autonomy, independence and competitive advantage. Therefore, the tool helps identify opportunities for value added from external flows to support the circular economy in rural properties.